Philosophy in education : questioning and dialogue in schools - Lone, Jana Mohr; Burroughs, Michael D. (Lanham, Maryland : Rowman & Littlefield, 2016)
Philosophy in Education: Questioning and Dialogue in Schools is a textbook in the fields of pre-college philosophy and philosophy of education, intended for philosophers and philosophy students, K-12 classroom teachers, administrators and educators, policymakers, and pre-college practitioners of all kinds. The book offers a wealth of practical resources for use in elementary, middle school, and high school classrooms, as well as consideration of many of the broader educational, social, and political topics in the field, including the educational value of pre-college philosophy, the philosophies of education that inform this philosophical practice, and the relevance of pre-college philosophy for pressing issues in contemporary education (such as education reform, child development, and prejudice and privilege in classrooms). The book includes sections on: the expansion of philosophy beyond higher education to pre-college populations; the importance of wondering, questioning and reflection in K-12 education; the ways that philosophy is uniquely suited to help students cultivate critical reasoning and independent thinking capacities; how to develop classroom communities of philosophical inquiry and their potentially transformative impact on students; the cultivation of philosophical sensitivity and positive identity formation in childhood; strategies for recognizing and diminishing the impact of social inequalities in classrooms; and the relationship between introducing philosophy in schools and education reform.
Part 1: Why introduce philosophy to young people? -- 1.Philosophy beyond the university -- 2.Wonder, questioning and reflection -- Part 2: Making space for questioning and dialogue -- 3.Learner-centered education and the dialogical model -- 4.Philosophical sensitivity -- 5.The community of philosophical inquiry -- Part 3: In the classroom -- 6.Philosophy in the classroom -- 7.Philosophy in middle school -- 8.Philosophy in high school -- Part 4: Identity, social inequality, and philosophical practice -- 9.Philosophical recognition and identity: recognizing the child -- 10.Children's philosophical encounters: taking seriously the role of privilege in classrooms -- 11.Philosophy and transforming precollege education.
Keywords: PHILOSOPHY -- STUDY AND TEACHING (ELEMENTARY)